Effect of polymers and waste cooking oil on asphalt performance range - Münkel Jiménez, Michelle (2025)
Permanent deformation and fatigue are the main problems on Costa Rica's highways, and these are directly related to the asphalt binder. This study seeks to define dosage ranges for polymers and Waste Cooking Oil (WCO) to improve the performance of modified asphalt by improving resistance to fatigue and permanent deformation. The used materials were then characterized. Tests were carried out to determine how the binder would interact with the WCO. Then, the different dosage combinations of both WCO and commercial polymer, SBS or RET in each sample of modified asphalt were selected based on the experimental design. Finally, the sample performance grades (PG) were measured, and their resistance to deformation was evaluated by advanced rheology testing. Waste cooking oil was found to lower the upper and lower limit of the PG. It was also evidenced that the presence of the WCO affects the interaction of the asphalt with the SBS. However, the upper limit of PG increased 2 degrees without affecting the intermediate and low temperatures for the samples modified with RET and oil. Based on the statistical analysis it was determined that the polymer used in each sample (SBS or RET) was the factor that generated the most significant differences in resistance to permanent deformation and fatigue. The elastic recovery was mostly influenced by the polymer dosage. It was also determined that the difference in the amount of WCO used in the samples of the experimental design did not generate significant changes in the measured variables. Finally, the polymer and WCO dosage ranges needed to reach the PGs required in Costa Rica were determined. Generally, the asphalt design guidelines used in the country are established to meet different requirements to those present in Costa Rica. Therefore, this study allows to lay the foundations of a guideline for the asphalt modification process and provides more detail on how to guarantee a good performance of national asphalt.